High-added value products from microalgae and prospects of aquaculture wastewaters as microalgae growth media. Issue 12 (14th May 2020) - Dourou, Marianna; Dritsas, Panagiotis; Baeshen, Mohamed N; Elazzazy, Ahmed; Al-Farga, Ammar; Aggelis, George
Abstract: Aquaculture plays an important role in human nutrition and economic development but is often expanded to the detriment of the natural environment. Several research projects, aimed at cultivating microalgae in aquaculture wastewaters (AWWs) to reduce organic loads and minerals, along with the production of microalgal cell mass and metabolic products, are underway. Microalgal cell mass is of high nutritional value and is regarded as a candidate to replace, partially at least, the fish meal in the fish feed. Also, microalgal cell mass is considered as a feedstock in the bio-fuel manufacture, as well as a source of high-added value metabolic products. The production of these valuable products can be combined with the reuse of AWWs in the light of environmental concerns related with the aquaculture sector. Many research papers published in the last decade demonstrate that plenty of microalgae species are able to efficiently grow in AWWs, mainly derived from fish and shrimp farms, and produce valuable metabolites reducing the AWW pollutant load. We conclude that bio-remediation of AWWs combining with the production of microalgae cell mass and specific metabolites is probably the most convenient and economical solution for AWWs management and can contribute to the sustainable growth of the aquaculture. Abstract : The valorization of aquaculture wastewaters as growth media for microalgae is of high significance increasing sustainability of both aquaculture and the production of microalgal bioactive compounds (e.g. lipids, vitamins, pigments).